Glucagon-induced extracellular cAMP regulates hepatic lipid metabolism. Issue 2 (August 2017) - Lv, Sihan; Qiu, Xinchen; Li, Jian; Liang, Jinye; Li, Weida; Zhang, Chao; Zhang, Zhen-Ning; Luan, Bing
Abstract : Hormonal signals help to maintain glucose and lipid homeostasis in the liver during the periods of fasting. Glucagon, a pancreas-derived hormone induced by fasting, promotes gluconeogenesis through induction of intracellular cAMP production. Glucagon also stimulates hepatic fatty acid oxidation but the underlying mechanism is poorly characterized. Here we report that following the acute induction of gluconeogenic genes Glucose 6 phosphatase ( G6Pase ) and Phosphoenolpyruvate carboxykinase ( Pepck ) expression through cAMP-response element-binding protein (CREB), glucagon triggers a second delayed phase of fatty acid oxidation genes Acyl-coenzyme A oxidase ( Aox ) and Carnitine palmitoyltransferase 1a ( Cpt1a ) expression via extracellular cAMP. Increase in extracellular cAMP promotes PPARα activity through direct phosphorylation by AMP-activated protein kinase (AMPK), while inhibition of cAMP efflux greatly attenuates Aox and Cpt1a expression. Importantly, cAMP injection improves lipid homeostasis in fasted mice and obese mice, while inhibition of cAMP efflux deteriorates hepatic steatosis in fasted mice. Collectively, our results demonstrate the vital role of glucagon-stimulated extracellular cAMP in the regulation of hepatic lipid metabolism through AMPK-mediated PPARα activation. Therefore, strategies to improve cAMP efflux could serve as potential new tools to prevent obesity-associated hepatic steatosis.